Institutional Trust in Kazakhstan: Regional Specifics (Journal of Philosophy Culture and Political Science, 2022)
Institutional trust is one of the significant factors of the stability of the state, so its study is pertinent in all conditions. Another reason why it is essential to research institutional trust may be the ability to determine the attitude of citizens to political power and to predict political attitude. There are many research papers on the topic of trust in various political institutions these days. But the regional aspect of trust of Kazakhstani citizens remains understudied. Therefore, this article aims to study and analyze the regional characteristics of institutional trust in Kazakhstan. Theoretical scientific works have allowed to consider the phenomenon of trust, its role and functions in the political system. Data from the World Values Survey (WVS) made it possible to determine the level of institutional trust of respondents in different regions of Kazakhstan and compare it with life satisfaction and financial situation of respondents, as well as with political participation and respondents' assessment of the involvement of public authorities in corruption. As a result, the specifics of how trust in institutions can be reflected in participation in various forms of political action were revealed. The article was written within the framework of the scientific project AP08857524 "Protest potential in Kazakhstan: features, factors, and trends".Keywords: institutional trust, political protest, political values, political participation.